Prevalence of alexithymia and its association with geriatric depression in a sample of elderly persons living in Buenos Aires, Argentina: Prevention (nonpharmacological) / Other. (7th December 2020) - Tartaglini, María Florencia; Hermida, Paula; Feldberg, Carolina; Somale, Maria Veronica; Caruso, Diego; Stefani, Dorina
Abstract: Background: Alexithymia has been considered a personality trait characterized by difficulties of identifying and describing feelings, and an externally oriented thinking style. Furthermore, has been descripted as a multidimensional concept sensitive at stressful environment. Moreover, the ageing is a period characterized by physical, affective and economics loses, where alexithymia seems to be a common feature of neurological disease. Objetive : To evaluate the prevalence of Alexithymia and its possible association with geriatric depression in elderly people self‐sufficient. Method: A simple retrospective, cross sectional, correlational study was conducted. A non‐probability, purposive sampling strategy was used. The sample was comprised of 300 older adults over sixty years old, living in Buenos Aires, Argentina. They were evaluated in individual interviews using the following measures: a socio‐demographic questionnaire ( ad hoc ), Latin American Consensual Toronto Alexithymia Scale LAC TAS‐20 and Geriatric Depression Scale (V‐15). Measures of central tendency and of dispersion were obtained to describe alexithymia and the Pearson's "r" correlation coefficient was used to measure the degree of association between alexithymia and geriatric depression. An error probability minor or equal to 0.05 was established. Data were analyzed by SPSS statistical software version 21.0. Result: The mean age was 71.71 year old (+ 7.34 years) and 76, 2% of the participants were women. The prevalence of Alexithymia was 53.1%, and the mean of total score was 45.41 (sd 17.55). The subscales scores were: DIF 14.55 (sd + 7.3), DDF 11.40 (sd + 6.0), EOT 19.45 (sd + 7.3). Furthermore, a moderate positive correlation was found between the alexithymia and geriatric depression ("r": .369, p: .000). Conclusion: Detecting alexithymia could be relevant for preserving the wellbeing of elderly people and diagnose diagnosticate affective disorders and neurological diseases.